Modified epoxy acrylate, preparation method thereof, conductive adhesive, preparation method and application thereof

Through the use of modified epoxy acrylate, the shortcomings of existing conductive adhesives in moisture resistance, aging resistance and curing process are solved, and high-strength, flexibility and moisture-heat resistance are achieved, which are suitable for flexible application scenarios.

CN119505176APending Publication Date: 2025-02-25SUZHOU ANTENG NANO TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411612081.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing conductive glue systems have shortcomings in moisture resistance, aging resistance, shear force and curing process, especially the problem of internal failure to cure when ultraviolet light is cured.

Method used

Modified epoxy acrylate is used, and its structure contains acrylic double bonds and epoxy groups. The curing is achieved through low-temperature thermal radical initiation and epoxy curing, and a long-chain structure is introduced to improve flexibility.

Benefits of technology

It has achieved improvements in curing strength and bonding strength, and has excellent flexibility, moisture and heat resistance and low stress performance. It is suitable for flexible application scenarios such as speaker diaphragm and semiconductor chip bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505176A_ABST
    Figure CN119505176A_ABST
Patent Text Reader

Abstract

The invention provides modified epoxy acrylate, a preparation method thereof, a conductive adhesive, a preparation method and application thereof, the structural formula of the modified epoxy acrylate is # imgabs0 #, R1 is H or CH3, R2 is # imgabs1 #, R3 is long-chain aliphatic hydrocarbon, R4 is # imgabs2 #, R5 in R4 is H or CH3; according to the present invention, the curing strength and the bonding strength can be increased, and the modified epoxy acrylate has the long-chain structure so as to provide the cured modified epoxy acrylate with excellent flexibility, such that the curing strength and the bonding strength can be improved; the conductive adhesive adopting the modified epoxy acrylate system disclosed by the invention has the excellent properties of low-temperature curing, flexibility, excellent heat and humidity resistance, high binding power, relatively good conductivity, low stress and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of adhesives, and in particular to a modified epoxy acrylate, a method for preparing the modified epoxy acrylate, a conductive adhesive having the modified epoxy acrylate, a method for preparing the conductive adhesive, and applications of the conductive adhesive. Background Art

[0002] With the miniaturization and micro-manufacturing of electronic components and the rapid development of integrated circuits, conductive adhesives are widely used in various fields as a means of fine connection.

[0003] Existing conductive adhesive systems include the following: 1) acrylic conductive adhesive. Acrylic conductive adhesive has the advantages of fast curing, high flexibility, and a wide Tg adjustment range, but its moisture resistance and aging resistance are poor, its shear force is low, and there is a problem of surface oxygen inhibition during curing. As a conductive adhesive, using acrylic light curing will cause problems such as UV light not being able to penetrate and internal curing not being possible; 2) epoxy conductive adhesive. Epoxy conductive adhesive has good adhesion and aging resistance, but its cured product has high hardness, poor flexibility, and high stress; 3) silicone conductive adhesive. Silicone conductive adhesive has good flexibility and heat resistance, but very poor adhesion. Summary of the invention

[0004] The object of the present invention is to provide a modified epoxy acrylate, a method for preparing the modified epoxy acrylate, a conductive adhesive having the modified epoxy acrylate, a method for preparing the conductive adhesive and applications of the conductive adhesive.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a modified epoxy acrylate, the structural formula of the modified epoxy acrylate is:

[0006] Wherein, R1 is H or CH3, R2 is R3 is a long chain aliphatic hydrocarbon, R4 is R5 in R4 is H or CH3.

[0007] To achieve the above object of the invention, the present invention also provides a method for preparing modified epoxy acrylate, comprising the following steps:

[0008] Mix hydroxyalkyl acrylate or hydroxyalkyl methacrylate, an acid anhydride with an alkyl long-chain structure, and a polymerization inhibitor, heat to 80° C. to 120° C., and react at a constant temperature until the acid value of the system remains unchanged to obtain an intermediate product;

[0009] Add epoxy resin or epoxy active diluent to the intermediate product, heat to 60-120° C., and react at a constant temperature until the epoxy value remains unchanged to obtain the modified epoxy acrylate.

[0010] As a further improvement of the present invention, the hydroxyalkyl acrylate or hydroxyalkyl methacrylate is at least one of 2-hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate.

[0011] As a further improvement of the present invention, the acid anhydride having an alkyl long-chain structure is at least one of succinic anhydride, glutaric anhydride, adipic anhydride, azelaic anhydride, tung oil anhydride, octenyl succinic anhydride, nonenyl succinic anhydride, decenyl succinic anhydride, dodecenyl succinic anhydride, and n-octadecyl succinic anhydride.

[0012] As a further improvement of the present invention, the inhibitor is at least one of hydroquinone, p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol and 2,5-di-tert-butylhydroquinone; and / or the epoxy resin is at least one of bisphenol A epoxy resin and bisphenol F epoxy resin; the epoxy reactive diluent is at least one of 2-EHA, IDA, LA, IBOA, IBOMA, HDDA, NPGDA, TEGDA, TMPTA, PETA, PETTA, DPPA and DPHA.

[0013] As a further improvement of the present invention, a catalyst is added while mixing hydroxyalkyl acrylate or hydroxyalkyl methacrylate, an acid anhydride having an alkyl long-chain structure, and a polymerization inhibitor. The catalyst is at least one of triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine, and tetraethylammonium bromide.

[0014] In order to achieve the above-mentioned object of the invention, the present invention further provides a conductive adhesive, comprising:

[0015] Modified epoxy acrylate: 5-15 parts by weight, wherein the modified epoxy acrylate is the modified epoxy acrylate in claim 1, or the modified epoxy acrylate is prepared by the preparation method of the modified epoxy acrylate in any one of claims 2 to 7;

[0016] 2 to 10 parts by weight of acrylic acid monomer;

[0017] 2 to 6 parts by weight of thermal free radical initiator;

[0018] 0.5-3 parts by weight of coupling agent;

[0019] 65-85 parts by weight of conductive filler;

[0020] 1-10 parts by weight of thermal curing agent;

[0021] 0.1 to 1 part by weight of curing accelerator;

[0022] Thixotropic agent 0-5 parts by weight.

[0023] As a further improvement of the present invention, the conductive filler is flaky silver powder with a D50 particle size less than 20 um; and / or, the conductive filler is spherical silver powder with a D50 particle size less than 10 um.

[0024] To achieve the above-mentioned object of the invention, the present invention also provides a method for preparing a conductive adhesive, comprising the following steps:

[0025] Add 5-15 parts by weight of modified epoxy acrylate, 2-10 parts by weight of acrylic monomer, 2-6 parts by weight of thermal free radical initiator, and 0.5-3 parts by weight of coupling agent into a stirring kettle, and stir for a first preset time under vacuum, wherein the modified epoxy acrylate is the modified epoxy acrylate of claim 1, or the modified epoxy acrylate is prepared by the preparation method of the modified epoxy acrylate of any one of claims 2 to 7;

[0026] Add 1-10 parts by weight of a thermal curing agent, control the temperature to be no higher than 30° C., and stir for a second preset time under a vacuum state;

[0027] Add 65-85 parts by weight of conductive filler, control the temperature to be no higher than 30° C., and stir for a third preset time under vacuum;

[0028] Add 0.1 to 1 parts by weight of a curing accelerator, control the temperature to be no higher than 25° C., and stir for a fourth preset time in a vacuum and light-proof state;

[0029] 0 to 5 parts of thixotropic agent are added, the temperature is controlled not to be higher than 25° C., and the conductive adhesive is obtained after stirring for a fifth preset time.

[0030] In order to achieve the above-mentioned purpose of the invention, the present invention also provides an application of the above-mentioned conductive adhesive in a loudspeaker.

[0031] The beneficial effects of the present invention are as follows: the modified epoxy acrylate in the present invention contains an acrylic double bond and an epoxy group at both ends, respectively, which can achieve an increase in curing strength and bonding strength. At the same time, the modified epoxy acrylate has a long chain structure, so that the modified epoxy acrylate after curing can have excellent flexibility. Therefore, the conductive adhesive using the modified epoxy acrylate system in the present invention has excellent properties such as low-temperature curing, flexibility, excellent moisture and heat resistance, high adhesion, good conductivity, low stress, etc., and can be used in flexible application scenarios to achieve low stress bonding to flexible substrates and bonding of semiconductor chips or LEDs. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a flow chart of the preparation method of the modified epoxy acrylate in the present invention;

[0033] Figure 2The flowchart of the method for preparing the conductive adhesive of the present invention is shown in FIG. DETAILED DESCRIPTION

[0034] The present invention will be described in detail below in conjunction with the various embodiments shown in the accompanying drawings. Figure 1-Figure 2 Shown is a preferred embodiment of the present invention.

[0035] The present invention provides a modified epoxy acrylate, the structural formula of which is:

[0036] Wherein, R1 is H or CH3, R2 is R3 is a long chain aliphatic hydrocarbon, R4 is R5 in R4 is H or CH3.

[0037] The modified epoxy acrylate of the present invention, on the one hand, contains an acrylic double bond and an epoxy group at both ends, respectively. The acrylic double bond can be cured at 85°C within 30 minutes or quickly cured at 100°C within 15 minutes under the initiation of a low-temperature thermal free radical initiator, and then thermally cured with the aid of an epoxy group. The epoxy group is ring-opened during curing to generate a hydroxyl group with strong polarity, which can improve the adhesion of the corresponding material, thereby achieving an increase in curing strength and bonding strength; on the other hand, the modified epoxy acrylate has It has a long-chain structure, that is, a long-chain aliphatic hydrocarbon R3, which can rotate freely, so that the cured modified epoxy acrylate can have excellent flexibility, bendability, and low stress, and can also increase the adhesion of the corresponding product to the substrate, thereby further increasing the adhesion, and is suitable for conductive adhesives used in flexible scenarios, such as speaker diaphragms, speaker elastic waves, etc.; and the modified epoxy acrylate has a rigid structure, such as the two benzene ring structures in R4, which makes the modified epoxy acrylate have excellent flexibility and good resistance to moisture and heat aging.

[0038] Specifically, R3 is a structure formed by the ring opening of an acid anhydride with a fatty long chain, that is, a structure formed by the ring opening of an acid anhydride with an alkyl long chain structure, and the number of carbon atoms in R3 is generally 4 to 30.

[0039] The acid anhydride with an alkyl long-chain structure is at least one of succinic anhydride, glutaric anhydride, adipic anhydride, azelaic anhydride, tung oil anhydride, octenyl succinic anhydride, nonenyl succinic anhydride, decenyl succinic anhydride, dodecenyl succinic anhydride and n-octadecyl succinic anhydride.

[0040] In a preferred embodiment, the acid anhydride having an alkyl long chain structure is dodecenyl succinic anhydride.

[0041] Combination Figure 1As shown, the present invention also provides a method for preparing modified epoxy acrylate, comprising the following steps:

[0042] S1: mixing hydroxyalkyl acrylate or hydroxyalkyl methacrylate, an acid anhydride having an alkyl long-chain structure, and a polymerization inhibitor, heating the mixture to 80° C. to 120° C., and reacting the mixture at a constant temperature until the acid value of the system remains unchanged, thereby obtaining an intermediate product;

[0043] S2: adding epoxy resin or epoxy active diluent to the intermediate product, heating to 60-120° C., and reacting at a constant temperature until the epoxy value remains unchanged to obtain modified epoxy acrylate.

[0044] In the preparation process of the modified epoxy acrylate of the present invention, the acid anhydride with long-chain alkanes reacts with epoxy resin to introduce the flexible chain segment into the main chain of epoxy resin to prepare the modified epoxy resin, and then the modified epoxy acrylate is obtained by acrylate esterification. Free radical polymerization can be initiated at low temperature, and can be further cured with an epoxy curing agent to achieve low-temperature rapid curing. At the same time, the cured product has high strength, high adhesion, good moisture and heat resistance, and aging resistance.

[0045] Specifically, the structural formula of the modified epoxy acrylate prepared by the above-mentioned preparation method in the present invention is: Wherein, R1 is H or CH3, R2 is R3 is a long chain aliphatic hydrocarbon, R4 is R5 in R4 is H or CH3. It can be seen that, on the one hand, the modified epoxy acrylate prepared in the present invention contains acrylic double bonds and epoxy groups at both ends respectively, and the acrylic double bonds can be cured at 85°C within 30 minutes or at 100°C within 15 minutes under the initiation of a low-temperature thermal free radical initiator, and then assisted by epoxy group curing, the curing strength and bonding strength can be increased; on the other hand, the modified epoxy acrylate has a long chain structure, so that the cured modified epoxy acrylate can have excellent flexibility, which is suitable for conductive adhesives used in flexible scenes to achieve bonding to flexible substrates, such as speaker diaphragms, speaker elastic waves, etc.; and the modified epoxy acrylate has a rigid structure, so that the modified epoxy acrylate has excellent flexibility and good resistance to wet heat aging.

[0046] In some optional embodiments, the hydroxyalkyl acrylate or hydroxyalkyl methacrylate in step S1 is at least one of 2-hydroxyethyl acrylate (HEA), hydroxypropyl acrylate (HPA), hydroxyethyl methacrylate (HEMA), and hydroxypropyl methacrylate (HPMA).

[0047] In a preferred embodiment, 2-hydroxyethyl acrylate (HEA) is selected in step S1. 2-Hydroxyethyl acrylate has a lower viscosity and a higher activity, which is conducive to uniform mixing of the components.

[0048] In some optional embodiments, the acid anhydride having an alkyl long-chain structure is at least one of succinic anhydride, glutaric anhydride, adipic anhydride, azelaic anhydride, tung oil anhydride, octenyl succinic anhydride, nonenyl succinic anhydride, decenyl succinic anhydride, dodecenyl succinic anhydride, and n-octadecyl succinic anhydride.

[0049] In a preferred embodiment, the acid anhydride having a long alkyl chain structure is dodecenyl succinic anhydride. Dodecenyl succinic anhydride has excellent flexibility and is not easy to crystallize.

[0050] In some optional embodiments, the polymerization inhibitor is at least one of hydroquinone, p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol and 2,5-di-tert-butylhydroquinone.

[0051] In a preferred embodiment, the inhibitor is p-hydroxyanisole or 2,6-di-tert-butyl-p-cresol, which has a good inhibitory effect, and the chromaticity of the intermediate product obtained after the reaction is low.

[0052] In some optional embodiments, in step S1, a catalyst is added while mixing hydroxyalkyl acrylate or hydroxyalkyl methacrylate, an acid anhydride having an alkyl long-chain structure, and a polymerization inhibitor to promote the ring-opening reaction of the acid anhydride having an alkyl long-chain structure.

[0053] Specifically, the catalyst is at least one of triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine, and tetraethylammonium bromide.

[0054] In a preferred embodiment, the catalyst is triphenylphosphine.

[0055] In some optional embodiments, the epoxy resin in step S2 is at least one of bisphenol A epoxy resin and bisphenol F epoxy resin.

[0056] Specifically, the epoxy resin can adopt existing commercially available products, such as: bisphenol A type epoxy resin can adopt YD-128 (Guodu Chemical), NPEL-128 (Nan Ya), EPICLON 850 (DIC), jER828EL (Mitsubishi Chemical Corporation), etc.; bisphenol F type epoxy resin can adopt NPEF-170 (Nan Ya), EPICOAT806, EPICOAT4004 (all manufactured by Japan Epoxy Resin Co., Ltd.), etc.

[0057] In some optional embodiments, the epoxy reactive diluent in step S2 is at least one of 2-EHA, IDA, LA, IBOA, IBOMA, HDDA, NPGDA, TEGDA, TMPTA, PETA, PETTA, DPPA and DPHA.

[0058] In a preferred embodiment, the epoxy reactive diluent is HDDA.

[0059] The present invention also provides a conductive adhesive prepared from the above-mentioned modified epoxy acrylate. The conductive adhesive in the present invention adopts the above-mentioned modified epoxy acrylate system, so that the conductive adhesive has excellent properties such as low-temperature curing, flexibility, excellent moisture and heat resistance, high adhesion, and good conductivity. It can be applied to flexible application scenarios to achieve low stress bonding to flexible substrates and semiconductor chips or LED bonding, such as speaker diaphragms, speaker elastic waves, etc.; at the same time, it can be cured at low temperature, overcoming the defect that the existing nano silver conductive adhesive layer cannot withstand the high temperature of solder.

[0060] Specifically, the conductive adhesive includes:

[0061] Modified epoxy acrylate: 5-15 parts by weight;

[0062] 2 to 10 parts by weight of acrylic acid monomer;

[0063] 2 to 6 parts by weight of thermal free radical initiator;

[0064] 0.5-3 parts by weight of coupling agent;

[0065] 65-85 parts by weight of conductive filler;

[0066] 1-10 parts by weight of thermal curing agent;

[0067] 0.1 to 1 part by weight of curing accelerator;

[0068] Thixotropic agent 0-5 parts by weight.

[0069] Wherein, the modified epoxy acrylate is a modified epoxy acrylate having the above structural formula, or the modified epoxy acrylate is prepared by the above preparation method, which will not be described in detail herein.

[0070] In the conductive adhesive of the present invention, by adopting the above-mentioned modified epoxy acrylate system, the conductive adhesive can be cured within 60°C to 100°C, that is, it has excellent properties such as low-temperature curing, flexibility, excellent moisture and heat resistance, high adhesion, and good conductivity. It can be used in flexible application scenarios to achieve low stress bonding to flexible substrates and semiconductor chips or LEDs, such as speaker diaphragms, speaker elastic waves, etc.

[0071] At the same time, the conductive adhesive of the present invention is added with a certain amount of acrylic monomer on the basis of the modified epoxy acrylate system, so as to adjust the final curing speed. In some optional embodiments, the thermal free radical initiator is selected from at least one of tert-butyl peroxyneodecanoate, tert-butyl peroxybenzoate, tert-butyl peroxyisooctanoate, tert-amyl peroxy(2-ethylhexanoate), dibenzoyl peroxide, and bis(4-tert-butylcyclohexyl) peroxydicarbonate.

[0072] In some optional embodiments, the coupling agent is at least one of KH-550, KH-560, KH-570, and KH-792.

[0073] In a preferred embodiment, the coupling agent is KH-570. KH-570 has an acryl structure and can participate in the curing of the organic system, thereby increasing compatibility and adhesion.

[0074] In some optional embodiments, the conductive filler is flaky silver powder with a D50 particle size less than 20um; and / or, the conductive filler is spherical silver powder with a D50 particle size less than 10um, which can avoid the problem of the dispensing needle being difficult to extrude due to being too large, or the problem of the conductive glue being difficult to dispense due to being too small in size.

[0075] In some optional embodiments, the thermal curing agent is at least one of a long-chain aliphatic dibasic acid polyanhydride with a side group, dodecenyl succinic anhydride, malonic acid dihydrazide, adipic acid dihydrazide or UDH-J of Ajinomoto Co., Ltd. These thermal curing agents are epoxy curing agents with flexible groups. Thus, on the basis of the flexible resin, the flexibility of the final cured product is further increased to achieve low stress bonding to the flexible substrate and semiconductor chip or LED bonding, and better cope with high and low temperature cycle thermal shock.

[0076] In some optional embodiments, the curing accelerator is at least one of 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30), diazabicyclic derivatives, 2-ethyl-4-methylimidazole, and NTCAT SA102 organic amine salt complex.

[0077] Combination Figure 2 As shown, the present invention also provides a method for preparing the above-mentioned conductive adhesive, comprising the following steps:

[0078] Sa, adding 5-15 parts by weight of modified epoxy acrylate, 2-10 parts by weight of acrylic monomer, 2-6 parts by weight of thermal free radical initiator, and 0.5-3 parts by weight of coupling agent into a stirring kettle, and stirring for a first preset time under vacuum, wherein the modified epoxy acrylate is the modified epoxy acrylate mentioned above, or the modified epoxy acrylate is prepared by the preparation method of the modified epoxy acrylate mentioned above;

[0079] Sb, add 1-10 parts by weight of a thermal curing agent, control the temperature to be no higher than 30° C., and stir for a second preset time under a vacuum state;

[0080] Sc, adding 65-85 parts by weight of conductive filler, controlling the temperature to be no higher than 30° C., and stirring for a third preset time under vacuum;

[0081] Sd, add 0.1 to 1 parts by weight of curing accelerator, control the temperature not higher than 25°C, and stir for a fourth preset time in a vacuum and light-proof state;

[0082] Se, add 0 to 5 parts of thixotropic agent, control the temperature not higher than 25° C., and stir for a fifth preset time to obtain the conductive adhesive.

[0083] In the preparation method of the conductive adhesive of the present invention, the liquid part of the conductive adhesive components is first mixed in step Sa, and then a thermosetting agent is added in a subsequent step. After the organic component is partially mixed, the conductive filler is added to facilitate uniform mixing of the components during the preparation process, making it easier to mix the conductive filler into the organic system and avoid heat generation.

[0084] In addition, in the preparation process of the conductive adhesive of the present invention, such as in steps Sb to Se, the reaction temperature is strictly controlled to avoid premature partial curing of the resin and the thermosetting agent due to temperature increase, which in turn leads to increased viscosity and decreased performance, and to avoid the overall viscosity stability of the conductive adhesive from deteriorating.

[0085] Specifically, after adding the components into the stirring kettle in step Sa, stirring is performed for 30 minutes under vacuum state, at revolution of 10 to 50 r / min and rotation of 600 to 1000 r / min, that is, the first preset time is 30 minutes.

[0086] After adding the heat curing agent in step Sb, the temperature is controlled not higher than 30° C., and stirring is performed for 30 minutes under a vacuum state and at a revolution of 10 to 50 r / min, that is, the second preset time is 30 minutes.

[0087] After adding the conductive filler in step Sc, the temperature is controlled not higher than 30° C., and stirring is performed for 30 to 60 minutes under vacuum and at a revolution of 10 to 50 r / min, that is, the third preset time is 30 to 60 minutes.

[0088] After adding the curing accelerator in step Sd, the temperature is controlled not higher than 25° C., and the mixture is stirred for 20 to 30 minutes under vacuum and light-proof conditions and at a revolution of 10 to 30 r / min, that is, the fourth preset time is 20 to 30 minutes.

[0089] In step Se, after adding the thixotropic agent, the temperature is controlled not to be higher than 25° C., and the conductive adhesive is obtained after stirring for 10 to 30 minutes at a revolution of 10 to 30 r / min. That is, the fifth preset time is 10 to 30 minutes.

[0090] The present invention also provides an application of the above conductive adhesive in a loudspeaker. Specifically, the conductive adhesive can be used for conductive bonding of a loudspeaker diaphragm or a loudspeaker elastic wave. Of course, it is understandable that the conductive adhesive is not limited to the above-mentioned loudspeaker. Its excellent flexibility, adhesion, conductivity, moisture and heat resistance, low stress, and low-temperature curing properties enable the conductive adhesive to be used for bonding flexible substrates or conductive connectors. For example, it can be used for chip bonding in the semiconductor field. While being able to achieve low-temperature curing, due to its low-stress characteristics, the chip can better disperse stress when responding to high and low temperature shocks, thereby preventing the occurrence of delamination failure.

[0091] The present invention will be described in detail with reference to specific embodiments. Of course, it should be understood that the embodiments of the present invention are not limited to the embodiments described below.

[0092] Examples 1 to 4 and Comparative Examples 1 to 2:

[0093] Embodiment 1:

[0094] The conductive adhesive in Example 1 includes:

[0095] Modified epoxy acrylate A-1: ​​10 parts by weight;

[0096] Acrylic acid monomer HDDA: 6 parts by weight;

[0097] Thermal free radical initiator LPO: 2 parts by weight;

[0098] Coupling agent KH560: 0.5 parts by weight;

[0099] Conductive filler - flake silver powder: 75 parts by weight;

[0100] Thermal curing agent - malonic acid dihydrazide: 5 parts by weight;

[0101] Curing accelerator DMP-30: 0.5 parts by weight;

[0102] Thixotropic agent TS720: 1 part by weight.

[0103] The above conductive adhesive components are added into a homogenizer in sequence according to the preparation method of the above conductive adhesive, and the conductive adhesive in Example 1 is obtained by controlling the homogenization temperature, rotation speed, stirring time, etc.

[0104] The preparation method of the modified epoxy acrylate A-1 in Example 1 is as follows:

[0105] Add 116 parts by weight of 2-hydroxyethyl acrylate, 0.3 parts by weight of p-hydroxyanisole, and 266 parts by weight of dodecenyl succinic anhydride into a reactive flask, heat to 100° C. and stir to react for 5 hours. When the final acid value of the reaction solution is measured to be unchanged, turn off the heating to stop the reaction and obtain an intermediate product.

[0106] Then, 340 parts by weight of bisphenol A epoxy resin (YD-128) was added to the intermediate product, and the mixture was heated to 100° C. for reaction. When the epoxy value was found to be unchanged, the heating was turned off to stop the reaction, and modified epoxy acrylate A-1 was obtained.

[0107] Embodiment 2:

[0108] The conductive adhesive in Example 2 includes:

[0109] Modified epoxy acrylate A-2: 10 parts by weight;

[0110] Acrylic acid monomer HDDA: 6 parts by weight;

[0111] Thermal free radical initiator LPO: 2 parts by weight;

[0112] Coupling agent KH560: 0.5 parts by weight;

[0113] Conductive filler - flake silver powder: 75 parts by weight;

[0114] Thermal curing agent - malonic acid dihydrazide: 5 parts by weight;

[0115] Curing accelerator DMP-30: 0.5 parts by weight;

[0116] Thixotropic agent TS720: 1 part by weight;

[0117] The above conductive adhesive components are added into a homogenizer in sequence according to the preparation method of the above conductive adhesive, and the conductive adhesive in Example 2 is obtained by controlling the homogenization temperature, rotation speed, stirring time, etc.

[0118] The preparation method of the modified epoxy acrylate A-2 in Example 2 is as follows:

[0119] Add 116 parts by weight of 2-hydroxyethyl acrylate, 0.3 parts by weight of p-hydroxyanisole, and 350 parts by weight of octadecene succinic anhydride into a reactive flask, heat to 100° C. and stir to react for 5 hours. When the final acid value of the reaction solution is measured to be unchanged, turn off the heating to stop the reaction and obtain an intermediate product.

[0120] Then, 340 parts by weight of bisphenol A epoxy resin (YD-128) was added to the intermediate product, and the mixture was heated to 100° C. for reaction. When the epoxy value was found to be unchanged, the heating was turned off to stop the reaction, and modified epoxy acrylate A-2 was obtained.

[0121] Embodiment 3:

[0122] The conductive adhesive in Example 3 includes:

[0123] Modified epoxy acrylate A-3: 10 parts by weight;

[0124] Acrylic acid monomer HDDA: 6 parts by weight;

[0125] Thermal free radical initiator LPO: 2 parts by weight;

[0126] Coupling agent KH560: 0.5 parts by weight;

[0127] Conductive filler - flake silver powder: 75 parts by weight;

[0128] Thermal curing agent - malonic acid dihydrazide: 5 parts by weight;

[0129] Curing accelerator DMP-30: 0.5 parts by weight;

[0130] Thixotropic agent TS720: 1 part by weight;

[0131] The above conductive adhesive components are added into a homogenizer in sequence according to the preparation method of the above conductive adhesive, and the conductive adhesive in Example 3 is obtained by controlling the homogenization temperature, rotation speed, stirring time, etc.

[0132] The preparation method of the modified epoxy acrylate A-3 in Example 3 is as follows:

[0133] Add 116 parts by weight of 2-hydroxyethyl acrylate, 0.3 parts by weight of p-hydroxyanisole, and 100 parts by weight of succinic anhydride into a reactive flask, heat to 100° C., and stir to react for 5 hours. When the final acid value of the reaction solution is measured to be unchanged, turn off the heating to stop the reaction and obtain an intermediate product.

[0134] Then, 340 parts by weight of bisphenol F epoxy resin (YD-170) was added to the intermediate product, and the mixture was heated to 100° C. for reaction. When the epoxy value was found to be unchanged, the heating was turned off to stop the reaction, and modified epoxy acrylate A-3 was obtained.

[0135] Embodiment 4:

[0136] The conductive adhesive in Embodiment 4 includes:

[0137] Modified epoxy acrylate A-4: 10 parts by weight;

[0138] Acrylic acid monomer HDDA: 6 parts by weight;

[0139] Thermal free radical initiator LPO: 2 parts by weight;

[0140] Coupling agent KH560: 0.5 parts by weight;

[0141] Conductive filler - flake silver powder: 75 parts by weight;

[0142] Thermal curing agent - malonic acid dihydrazide: 5 parts by weight;

[0143] Curing accelerator DMP-30: 0.5 parts by weight;

[0144] Thixotropic agent TS720: 1 part by weight;

[0145] The above conductive adhesive components are added into a homogenizer in sequence according to the preparation method of the above conductive adhesive, and the conductive adhesive in Example 4 is obtained by controlling the homogenization temperature, rotation speed, stirring time, etc.

[0146] The preparation method of the modified epoxy acrylate A-4 in Example 4 is as follows:

[0147] Add 130 parts by weight of 2-hydroxyethyl methacrylate, 0.3 parts by weight of p-hydroxyanisole, and 266 parts by weight of dodecenyl succinic anhydride into a reactive flask, heat to 100° C., and stir to react for 5 hours. When the final acid value of the reaction solution is measured to be unchanged, turn off the heating to stop the reaction and obtain an intermediate product.

[0148] Then, 340 parts by weight of bisphenol F epoxy resin (YD-170) was added to the intermediate product, and the mixture was heated to 100° C. for reaction. When the epoxy value was found to be unchanged, the heating was turned off to stop the reaction, and modified epoxy acrylate A-4 was obtained.

[0149] Comparative Example 1:

[0150] The conductive adhesive in Comparative Example 1 includes:

[0151] Commercially available modified epoxy acrylate ALLNEX 3605: 10 parts by weight, the structural formula of which is as follows:

[0152]

[0153] Acrylic acid monomer HDDA: 6 parts by weight;

[0154] Thermal free radical initiator LPO: 2 parts by weight;

[0155] Coupling agent KH560: 0.5 parts by weight;

[0156] Conductive filler - flake silver powder: 75 parts by weight;

[0157] Thermal curing agent - malonic acid dihydrazide: 5 parts by weight;

[0158] Curing accelerator DMP-30: 0.5 parts by weight;

[0159] Thixotropic agent TS720: 1 part by weight;

[0160] The conductive adhesive components are sequentially added into a homogenizer according to the preparation method of the conductive adhesive, and the conductive adhesive in Comparative Example 1 is obtained by controlling the homogenization temperature, rotation speed, stirring time, etc.

[0161] Comparative Example 2:

[0162] The conductive adhesive in Comparative Example 2 includes:

[0163] Commercially available epoxy acrylate ALLNEX 3700: 5 parts by weight, its structural formula is as follows:

[0164]

[0165] Commercially available epoxy resin YD128: 5 parts by weight;

[0166] Acrylic acid monomer HDDA: 6 parts by weight;

[0167] Thermal free radical initiator LPO: 2 parts by weight;

[0168] Coupling agent KH560: 0.5 parts by weight;

[0169] Conductive filler - flake silver powder: 75 parts by weight;

[0170] Thermal curing agent - malonic acid dihydrazide: 5 parts by weight;

[0171] Curing accelerator DMP-30: 0.5 parts by weight;

[0172] Thixotropic agent TS720: 1 part by weight;

[0173] The above conductive adhesive components are added into a homogenizer in sequence according to the preparation method of the above conductive adhesive, and the conductive adhesive in Comparative Example 2 is obtained by controlling the homogenization temperature, rotation speed, stirring time, etc.

[0174] The conductive adhesives prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to performance tests. Specifically, the performance evaluation method was as follows:

[0175] (1) Curing speed: The prepared conductive adhesive was cured in an oven at 85°C for 30 minutes. After taking it out, the surface was touched with a finger to observe the surface curing condition, and the hardness was tested with a Shore hardness tester. The hardness test method was determined in accordance with the test method of GB / T 2411. Among them, if there was no surface stickiness and the hardness after curing was greater than D75, it was a fast curing speed, marked as ◎; if there was surface stickiness and the hardness after curing was less than D45, it was a poor curing speed, marked as ×; if it was between the two, marked as ▲.

[0176] (2) Young's modulus: DMA test was used with a heating rate of 3°C / min and a frequency of 1 Hz. A Young's modulus higher than 1000 MPa was considered high and marked as ×, and a Young's modulus lower than 500 MPa was considered excellent and marked as ◎. The values ​​between the two were marked as ▲.

[0177] (3) Bond strength: Test according to GB / T 7124 to test the bonding strength of PEEK. Specifically, use a universal material testing machine to test the tensile shear strength. Clamp the sample symmetrically on the fixture, with the clamping point 50 mm away from the bonding end. The tensile machine stretches at a constant speed of 50 mm / min until the bonded sample is broken. Record the load and convert it into N / mm based on force / bonding area. 2 , which is MPa; among them, for PEEK-PEEK shear strength greater than 5MPa, it is excellent and marked as ◎, less than 2MPa is marked as ×, and between is directly marked as ▲.

[0178] (4) Volume resistivity: The volume resistivity is tested at an ambient temperature of 23±2°C and a humidity of 50±5%RH using a four-probe tester (SZT-2A) in accordance with the test standard ASTM D257-2014 Test method for DC resistance or conductivity of insulating materials. A volume resistivity lower than 1*10-4Ω.cm is considered excellent, and higher than 1*10-3 is considered poor.

[0179] The properties of the conductive adhesives in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1 below:

[0180] Table 1

[0181]

[0182] From the test evaluation of the examples and comparative examples in Table 1, it can be seen that the conductive adhesive prepared by the modified epoxy acrylate of the present invention has excellent curing speed, adhesion, flexibility and high conductivity compared with the conductive adhesive prepared by ordinary epoxy acrylate.

[0183] Comparing Example 3 with Comparative Example 1, it can be seen that the content of the acid anhydride (succinic anhydride) with an alkyl long-chain structure in the modified epoxy acrylate in Example 3 is relatively low, resulting in poor adhesion and flexibility of the conductive adhesive obtained in Example 3.

[0184] In summary, the modified epoxy acrylate in the present invention contains an acrylic double bond and an epoxy group at both ends, respectively, which can increase the curing strength and bonding strength. At the same time, the modified epoxy acrylate has a long chain structure, so that the modified epoxy acrylate after curing can have excellent flexibility. Therefore, the conductive adhesive using the modified epoxy acrylate system in the present invention has excellent properties such as low-temperature curing, flexibility, excellent moisture and heat resistance, high adhesion, and good conductivity. It can be used in flexible application scenarios to achieve low stress bonding to flexible substrates and semiconductor chips or LED bonding, such as speaker diaphragms, speaker elastic waves, etc.

[0185] At the same time, the conductive silver paste in the present invention includes silver powder with a large surface area and nano silver wires with high conductivity and good flexibility. The combination of the two can achieve a balance between the conductive properties and mechanical properties of the conductive silver paste, and reduce the silver content. The overall viscosity of the conductive silver paste is low, which reduces the overall cost of the sheet and is beneficial to cost reduction and efficiency improvement of the final product.

[0186] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0187] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A modified epoxy acrylate, characterized in that: The structural formula of the modified epoxy acrylate is: Wherein, R1 is H or CH3, R2 is R3 is a long chain aliphatic hydrocarbon, R4 is R5 in R4 is H or CH3.

2. A method for preparing modified epoxy acrylate, characterized in that: The steps include: Mix hydroxyalkyl acrylate or hydroxyalkyl methacrylate, an acid anhydride with an alkyl long-chain structure, and a polymerization inhibitor, heat to 80° C. to 120° C., and react at a constant temperature until the acid value of the system remains unchanged to obtain an intermediate product; Add epoxy resin or epoxy active diluent to the intermediate product, heat to 60-120° C., and react at a constant temperature until the epoxy value remains unchanged to obtain modified epoxy acrylate.

3. The method for preparing modified epoxy acrylate according to claim 2, characterized in that: The hydroxyalkyl acrylate or hydroxyalkyl methacrylate is at least one of 2-hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate.

4. The method for preparing modified epoxy acrylate according to claim 2, characterized in that: The acid anhydride having an alkyl long-chain structure is at least one of succinic anhydride, glutaric anhydride, adipic anhydride, azelaic anhydride, tung oil anhydride, octenyl succinic anhydride, nonenyl succinic anhydride, decenyl succinic anhydride, dodecenyl succinic anhydride and n-octadecyl succinic anhydride.

5. The method for preparing modified epoxy acrylate according to claim 2, characterized in that: The inhibitor is at least one of hydroquinone, p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol and 2,5-di-tert-butylhydroquinone; and / or the epoxy resin is at least one of bisphenol A epoxy resin and bisphenol F epoxy resin; the epoxy reactive diluent is at least one of 2-EHA, IDA, LA, IBOA, IBOMA, HDDA, NPGDA, TEGDA, TMPTA, PETA, PETTA, DPPA and DPHA.

6. The method for preparing modified epoxy acrylate according to claim 2, characterized in that: A catalyst is added while mixing hydroxyalkyl acrylate or hydroxyalkyl methacrylate, an acid anhydride having an alkyl long-chain structure and a polymerization inhibitor. The catalyst is at least one of triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine and tetraethylammonium bromide.

7. A conductive adhesive, characterized in that: include: Modified epoxy acrylate: 5-15 parts by weight, wherein the modified epoxy acrylate is the modified epoxy acrylate in claim 1, or the modified epoxy acrylate is prepared by the preparation method of the modified epoxy acrylate in any one of claims 2 to 7; 2 to 10 parts by weight of acrylic acid monomer; 2 to 6 parts by weight of thermal free radical initiator; 0.5-3 parts by weight of coupling agent; 65-85 parts by weight of conductive filler; 1-10 parts by weight of thermal curing agent; 0.1 to 1 part by weight of curing accelerator; Thixotropic agent 0-5 parts by weight.

8. The conductive adhesive according to claim 7, characterized in that: The conductive filler is flaky silver powder with a D50 particle size of less than 20 um; and / or, the conductive filler is spherical silver powder with a D50 particle size of less than 10 um.

9. A method for preparing a conductive adhesive, characterized in that: The steps include: Add 5-15 parts by weight of modified epoxy acrylate, 2-10 parts by weight of acrylic monomer, 2-6 parts by weight of thermal free radical initiator, and 0.5-3 parts by weight of coupling agent into a stirring kettle, and stir for a first preset time under vacuum, wherein the modified epoxy acrylate is the modified epoxy acrylate in claim 1, or the modified epoxy acrylate is prepared by the preparation method of the modified epoxy acrylate in any one of claims 2 to 6; Add 1-10 parts by weight of a thermal curing agent, control the temperature to be no higher than 30° C., and stir for a second preset time under a vacuum state; Add 65-85 parts by weight of conductive filler, control the temperature to be no higher than 30° C., and stir for a third preset time under vacuum; Add 0.1 to 1 parts by weight of a curing accelerator, control the temperature to be no higher than 25° C., and stir for a fourth preset time in a vacuum and light-proof state; 0 to 5 parts of thixotropic agent are added, the temperature is controlled not to be higher than 25° C., and the conductive adhesive is obtained after stirring for a fifth preset time.

10. An application of conductive adhesive in a speaker, characterized in that: The conductive adhesive is the conductive adhesive in claim 7 or 8; or, the conductive adhesive is prepared by the method for preparing the conductive adhesive in claim 9.

Citation Information

Cited By

  • Conductive adhesive and preparation method thereof

    CN120173542B